2019
DOI: 10.1002/chem.201900963
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium‐Catalyzed Pauson–Khand‐Type Cyclization of 1,5‐Allene‐Alkynes: A Chirality Transfer Strategy for Optically Active Bicyclic Ketones

Abstract: An efficient chirality transfer in the [RhCl(CO) 2 ] 2catalyzed [2+ +2+ +1] cyclization of optically active axially chiral 1,3-disubstituted allenynes with CO to access optically active bicyclopentenone compoundsh as been developed. The distal C=Cb ondo fallenesr eactedw ith the alknye unit and CO to afford [4.3.0]-bicyclic products with high ee values under mild reaction conditions with an excellent selectivity. Scheme1.Some typicalb ioactiveand natural compounds containingac yclopentenone unit.Scheme2.Rhodiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…used a chirality transfer strategy to synthesize optically active bicyclopentenones 67 in 64%—97% yields with 90%—96% ee values through a Rh‐catalyzed [2 + 2 + 1] cyclization of optically active axially chiral 1,3‐disubstituted yne‐allenes 66 with CO (Scheme 21). [ 78 ] Various chiral TsN‐, (CO 2 Me) 2 C‐ and O‐linked yne‐allenes 66 and internal alkyne possessing alkyl, aryl, silyl substituents are suitable for this reaction, affording the target [4.3.0]‐bicyclic products by utilizing [RhCl(CO) 2 ] 2 and AgSbF 6 as co‐catalyst.…”
Section: Synthesis Of Carbocyclesmentioning
confidence: 99%
“…used a chirality transfer strategy to synthesize optically active bicyclopentenones 67 in 64%—97% yields with 90%—96% ee values through a Rh‐catalyzed [2 + 2 + 1] cyclization of optically active axially chiral 1,3‐disubstituted yne‐allenes 66 with CO (Scheme 21). [ 78 ] Various chiral TsN‐, (CO 2 Me) 2 C‐ and O‐linked yne‐allenes 66 and internal alkyne possessing alkyl, aryl, silyl substituents are suitable for this reaction, affording the target [4.3.0]‐bicyclic products by utilizing [RhCl(CO) 2 ] 2 and AgSbF 6 as co‐catalyst.…”
Section: Synthesis Of Carbocyclesmentioning
confidence: 99%
“…Thus, it was predicted that an intramolecular Pauson–Khand reaction with enantioenriched sulfonamides 1 would be a chirality transfer reaction but not a diastereoselective reaction. Although a chirality transfer Pauson–Khand reaction with enantioenriched allene derivatives has previously been reported, as far as we know, a reaction with atropisomeric substrates remains unknown.…”
mentioning
confidence: 99%
“…Tg’s bioactivity and molecularly complex 5,7,5-ring system have captured the interest of the synthetic community with three total syntheses and several synthetic approaches. Tg analogues have been prepared to understand the pharmacophoric groups that are important for biological activity. , However, these analogues are mostly accessed semisynthetically, limiting both their structural diversity and structure–activity relationship studies. Moreover, Tg’s interesting biological activity motivates a continuing search for analogues having potent activity that are less toxic. To this end, we have previously shown that racemic allene-yne 6 undergoes an allenic Pauson–Khand reaction (APKR) to give the enantioenriched 5,7-ring system ( R )- 7 via a stereoconvergent dynamic kinetic asymmetric transformation (DyKAT) process (Scheme b). , Herein, we report rapid access to the enantioenriched 5,7,5-ring system of Tg using this APKR strategy and describe our continuing investigations with the aim of understanding the influence of the allene-yne precursor on the yield and enantioselectivity of the stereoconvergent APKR, specifically, groups on the alkyne terminus, tether, and allene (Scheme c).…”
mentioning
confidence: 99%